Subclinical avian influenza A(H5N1) virus infection in human, Vietnam. - Le, M; Horby, P; Fox, A; Nguyen, H; Le Nguyen, H; Hoang, P; Nguyen, K; Jong, d; Jeeninga, R; Rogier van Doorn, H; Farrar, J; Wertheim, H (2013)
Laboratory-confirmed cases of subclinical infection with avian influenza A(H5N1) virus in humans are rare, and the true number of these cases is unknown. We describe the identification of a laboratory-confirmed subclinical case in a woman during an influenza A(H5N1) contact investigation in northern Vietnam.